Optimized barley phytase gene expression by focused FIND-IT screening for mutations in cis-acting regulatory elements - Madsen, Claus Krogh; Brearley, Charles Alistair; Harholt, Jesper; Brinch-Pedersen, Henrik (Frontiers in Plant Science, 2024)
Induced modification of plant gene expression is of both fundamental and applied importance. Cisacting regulatory elements (CREs) are major determinants of the spatiotemporal strength of gene expression. Yet, there are few examples where induced genetic variation in predetermined CREs has been exploited to improve or investigate crop plants. Here, we have applied the FIND-IT technology to discover CRE mutants in the promoter of the nutritional important barley grain phytase (PAPhy_a) gene. Mutants with higher or lower gene expression and ultimately higher or lower mature grain phytase activity (MGPA), respectively, were discovered. Field trials and inositol phosphate profiling during germination showed that PAPhy_a does not influence agronomic performance under the trial conditions but it do shorten the lag time of phosphate mobilization during germination. Higher endogenous MGPA is an improvement of the grain quality for feed use as it improves the phosphate bioavailability for monogastric animals. Moreover, as the targeted CRE motifs of the PAPhy_a promoter are shared with a range of seed expressed genes like key cereal and legume storage genes, the current results demonstrates a concept for modulating individual gene expression levels of a range of seed genes.